IMPLEMENTASI LEAN SIX SIGMA DALAM MENGURANGI BREAKDOWN MAINTENANCE PADA SISTEM AUTOMATIC LENGTH CONTROL DI PT XYZ MENGGUNAKAN METODE DMADV - Sandi Ruwiyanto; Rifan Rizwan; Thyar Romadhon; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
PT XYZ is a private company engaged in steel manufacturing, one of the products produced by this company is tire cord. This product is in the form of steel wire that serves to maintain the shape of the tire. The length of the wire is a very critical factor in quality, because one coil of wire that is not suitable length will cause a lot of scrap in consumers, namely the company that produces tires and of course this will cause customer complaints and customer dissatisfaction. Therefore, it is contained in the Automatic Length Control system to avoid the possibility of wire coils that are not suitable for delivery to customers. Every system must have weaknesses that lead to failure that causes maintenance breakdown. This study used the DMADV method to reduce breakdown maintenance on the Automatic Length Control system at PT XYZ. After going through all the stages using the DMADV method (Define, Measure, Analyze, Design, and Verify) a significant reduction in the number of breakdowns was obtained. Reduction of ALC-related breakdown maintenance by 88.1% or from 185 breakdowns to only 22 breakdowns. So that this flat pulley design was successful in reducing alc problems in henxing machines that produce tyre cord construction 3 +9 +15x0,23 +0.15 NT 6/12/18/5 SSZS